2007
DOI: 10.1074/jbc.m704458200
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Kinetic Studies of Y114F and W116F Mutants of Me2SO Reductase from Rhodobacter capsulatus

Abstract: Mutants of the active site residues Trp-116 and Tyr-114 of the molybdenum-containing Me 2 SO reductase from Rhodobacter capsulatus have been examined spectroscopically and kinetically. The Y114F mutant has an increased rate constant for oxygen atom transfer from Me 2 SO to reduced enzyme, the result of lower stability of the E red ⅐Me 2 SO complex. The absorption spectrum of this species (but not that of either oxidized or reduced enzyme) is significantly perturbed in the mutant relative to wildtype enzyme, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…[40,41] Given that the iso-lated form of the W116F mutant of DMSOR from Rhodobacter capsulatus showed a five-coordinate structure, accompanied by dissociation of the Q pterin from the molybdenum, the hydrogen bond involving the tryptophan residue has been considered to stabilise the Mo-S bond, [42] whereas the Mo-S bond is recovered in the catalytic cycle. [6] Stabilisation by hydrogen bonding is reasonably explained in the present study. Such interactions should be stabilised in the hydrophobic environment around the active site of the enzyme [2] as well as in our model complex.…”
Section: Biological Relevancesupporting
confidence: 59%
See 2 more Smart Citations
“…[40,41] Given that the iso-lated form of the W116F mutant of DMSOR from Rhodobacter capsulatus showed a five-coordinate structure, accompanied by dissociation of the Q pterin from the molybdenum, the hydrogen bond involving the tryptophan residue has been considered to stabilise the Mo-S bond, [42] whereas the Mo-S bond is recovered in the catalytic cycle. [6] Stabilisation by hydrogen bonding is reasonably explained in the present study. Such interactions should be stabilised in the hydrophobic environment around the active site of the enzyme [2] as well as in our model complex.…”
Section: Biological Relevancesupporting
confidence: 59%
“…[4,[7][8][9] In the active site, the conserved tryptophan (Trp) residue forms an NH···O=Mo hydrogen bond, which stabilises the coordination of the Q pterin to the Mo VI centre, but does not significantly affect the enzymatic activity. [6] Similar hydrogen bonds involving a histidine residue have been reported for the members of the DMSOR family. [10,11] A number of models of the DMSOR family have been reported, [12] and model complexes containing ligands closely related to MPT have recently been synthesised.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Mutagenesis studies of Tyr 114 385 and Trp 116 385b have probed the catalytic roles of these residues. Trp 116 is within hydrogen-bonding distance of the Mo=O of oxidized enzyme, and Tyr 114 (which is a valine in the otherwise closely related TMAO reductase from Shewanella massilia , see below) has been proposed to hydrogen bond to the oxygen of DMSO in the course of its reaction with reduced enzyme.…”
Section: The Dmso Reductase Familymentioning
confidence: 99%
“…The calculated barrier is somewhat too large, compared to experiments, 62 kJ/mol. 10,69 The reason for this is partly the DFT functional, partly the omission of the surrounding enzyme. Calibration calculations with the local CCSD(T0) method have shown that energies calculated with the current methodology have errors of 19-45 kJ/mol for the reaction mechanism of DMSOR.…”
Section: The Dmsor-dmso Reactionmentioning
confidence: 99%